Kajian Evaluasi Pelaksanaan Hari Bebas Kendaraan Bermotor (HBKB) Kota Surakarta dan Solo Car Free Day - Viriani Noviasari Dewi; Didik Setiyawan; Purwanto Purwanto; Fajar Hanung Basworo (Badan Riset dan Inovasi Daerah Kota Surakarta, 2023)
The development of a city can be seen from the number of road users in the area. The high mobility of the population makes many choices of modes of transportation to move from one place to another. Public and private transportation that develops side by side makes vehicle exhaust emissions increase. This increase can be felt by residents with an increasingly crowded city atmosphere. It is recorded that there is an increase in vehicle exhaust emissions by 15% annually in the City of Solo. This needs to be a common concern to care for and preserve the urban environment.